Factors Hindering the Implementation of Mediation in Minor Criminal Cases at the Gorontalo City Police Headquarters - Asyawati Kasim; Dian Ekawaty Ismail; Apripari (Catalist Indo Publisher, 2026)
The conventional criminal justice system, which focuses on punishment, causes a backlog of cases and lengthy proceedings, making restorative justice through penal mediation an alternative for resolving minor criminal offenses (TPR) based on Perkap No. 8 of 2021. This study aims to identify the main factors that hinder the implementation of mediation in MOC cases such as petty theft, minor assault, and defamation at the Gorontalo City Police Station, using a sociological empirical legal approach with primary data from interviews with investigator Brigpol Fier P. Simanjuntak, as well as secondary data from legal documents, analyzed qualitatively through reduction, classification, and interpretation. The results of the study show that the main obstacles include the strict formal requirements of Perkap No. 8 of 2021, disagreement between the parties (victim or perpetrator due to trauma or refusal of responsibility), family intervention that causes emotional or cultural pressure, and financial constraints such as inability to pay restitution and operational costs, with internal factors such as investigator human resources and bureaucracy being more dominant than external factors. Overall, mediation has not been optimal due to ineffectiveness in terms of legal substance, law enforcement, facilities, society, and legal culture. Recommendations include more flexible regulations, mediator training, state financial support, socialization of restorative justice, and integration of local values to improve effectiveness and social justice.